The Effect of Change Management on The Quality of Management Accounting Information - Winwin Yadiati, Ayke Nuraliati, Peny Cahaya Azwari, (Opción, 2019)
The purpose of this research is to test the influence of change management on the quality of management information system and its impact on the quality of management accounting information. The research method used is explanatory research and the data used is primary data through a questionnaire. The study found that change management affects the quality of management accounting information system and its impact on the quality of management accounting information. In conclusion, the quality of management accounting information system positively affects the quality of management accounting information.